THE USE OF FOREIGN EXPERIENCE IN IMPROVING THE EFFICIENCY OF BUDGET ENTERPRISES - Dosent., Nazirov Abduvosi Halimovich (Scholar Express Journals, 2023)
In the article, The President of the Republic of Uzbekistan Sh.Mirziyoyev, in his Message to the «Oliy Majlis» dated December 20, 2022, stressed the need to further enhance the role and responsibility of executive and representative bodies in local government, create a new system for monitoring the results of the activities of territorial structures of the Republic of Uzbekistan. ministries and departments develop criteria for evaluating their activities in public administration bodies and organizations, study international experience and the effective use of modern management technologies
Keywords: public administration; efficiency indicators; technologies